Emergent vortices at a ferromagnetic superconducting oxide interface - Petrović, A P (2014)
Understanding the cohabitation arrangements of ferromagnetism and superconductivity at the LaAlO3/SrTiO3 interface remains an open challenge. Probing this coexistence with sub-Kelvin magnetotransport experiments, we demonstrate that a hysteretic in-plane magnetoresistance develops below the superconducting transition for H < 0.15 T, independently of the carrier density or oxygen annealing. This hysteresis is argued to arise from vortex depinning within a thin (< 20 nm) superconducting layer, mediated by discrete ferromagnetic dipoles located solely above the layer. The pinning strength may be modified by varying the superconducting channel thickness via electric field-effect doping. No evidence is found for bulk magnetism or finite-momentum pairing, and we conclude that ferromagnetism is strictly confined to the interface, where it competes with superconductivity. Our work indicates that oxide interfaces are ideal candidate materials for the growth and analysis of nanoscale superconductor/ferromagnet hybrids.